O constitucionalismo abusivo na Justiça Constitucional brasileira: um diagnóstico sobre o abuso constitucional na prática do Supremo Tribunal Federal - Oliveira, Lucas Soares de (2023)
This paper aims to examine the occurrence of the phenomenon of abusive constitutionalism in the performance of the Brazilian Supreme Court (STF). The purpose of the text is to investigate and diagnose whether, in fact, abusive constitutionalism has been perpetrated by the Brazilian Constitutional Court, notably through its role as a player within the political arena. Methodologically, the work uses descriptive, exploratory, interpretative, and indirect empirical techniques. The subject is relevant, as it raises the creation of tools to guide discussions on corrections of democratic dysfunctionalities inherent to the action of the STF. The work is structured in four distinct parts. The first takes care of establishing the theoretical bases that allow understanding the scope of the expression “constitutionalism”. In the second, care is taken to expose in a warmer way a list of deviant constitutionalism’s, bringing the academic contributions originated from the reflection developed by several authors around the world. In the third part, already established the concept of abusive constitutionalism to be used, the work seeks to analyze other key pieces relevant to the development of the investigation, namely: “constitutional jurisdiction”, “constitutional justice” and “Constitutional Court”. The critical point of the work is reached in its fourth part. At this moment, the combination of elements worked on in the previous phases emerges, converging to the specific analysis of the constitutional practice carried out by the STF. Still in the fourth part of the work, decisions effectively taken by the STF and that symbolize the occurrence of abusive constitutionalism in the Brazilian constitutional justice are worked on. At the end of the four parts of the development of the work, the diagnosis of the situation is gathered in the final considerations